Letalidade por Síndrome Respiratória Aguda Grave por COVID 19 em indígenas hospitalizados no estado do Amazonas, 2020 - 2021 - Ferezin, Suellen Moura Rocha (2023)
Several studies reveal that the indigenous population has worse health indicators when compared to non-indigenous. With the COVID-19 pandemic and the socio-economic vulnerability to which they are exposed, indigenous peoples have been hit hard. The objective was to evaluate the lethality in reported cases of Severe Acute Respiratory Syndrome (SARS) due to COVID-19 in indigenous people hospitalized in the state of Amazonas and to describe the epidemiological and clinical characteristics of the patients. This is a prognostic study, based on data secondary data available in the Information Technology Department of the Unified Health System (DATASUS), obtained from notifications from the Influenza Epidemiological Surveillance Information System (SIVEP-Gripe) in the years 2020-2021. The case fatality rate was calculated and Cox regression was performed to determine prognostic factors associated with death. It was observed that the mortality rate due to SARS due to COVID-19 in hospitalized indigenous people (32.4%) was higher than that in non- indigenous people (31%) in Brazil and in the North region (35.2% and 34.1%). %, respectively), but the difference was not statistically significant. In the state of Amazonas, the fatality rate was higher in the non-indigenous population (34.4%) compared to the indigenous population (32%), but the result was not statistically significant. Age over 50 years was a worse prognostic factor associated with death among indigenous people (HR, 3.31 [95% CI, 2.42-4.52]; p < 0.001) and was a better prognostic factor associated with death having been hospitalized with symptoms lasting more than 7 days (HR, 0.53 [95% CI, 0.41-0.68]; p < 0.001). Public health policies must encompass the peculiarities that involve indigenous peoples